The effect of radiofrequency electromagnetic fields (RF-EMF) on biomarkers of oxidative stress in vivo and in vitro: A protocol for a systematic review. (January 2022) - Henschenmacher, Bernd; Bitsch, Annette; de las Heras Gala, Tonia; Forman, Henry Jay; Fragoulis, Athanassios; Ghezzi, Pietro; Kellner, Rupert; Koch, Wolfgang; Kuhne, Jens; Sachno, Dmitrij; Schmid, Gernot; Tsaioun, Katya; et al.
Graphical abstract: Abstract: Background: Oxidative stress is conjectured to be related to many diseases. Furthermore, it is hypothesized that radiofrequency fields may induce oxidative stress in various cell types and thereby compromise human and animal health. This systematic review (SR) aims to summarize and evaluate the literature related to this hypothesis. Objectives: The main objective of this SR is to evaluate the associations between the exposure to radiofrequency electromagnetic fields and oxidative stress in experimental models ( in vivo and in vitro ). Methods: The SR framework has been developed following the guidelines established in the WHO Handbook for Guideline Development and the Handbook for Conducting a Literature-Based Health Assessment). We will include controlled in vivo and in vitro laboratory studies that assess the effects of an exposure to RF-EMF on valid markers for oxidative stress compared to no or sham exposure. The protocol is registered in PROSPERO. We will search the following databases: PubMed, Embase, Web of Science Core Collection, Scopus, and the EMF-Portal. The reference lists of included studies and retrieved review articles will also be manually searched. Study appraisal and synthesis method: Data will be extracted according to a pre-defined set of forms developed in the DistillerSR online software and synthesized in a meta -analysis when studies are judged sufficiently similar to be combined. If a meta -analysis is not possible, we will describe the effects of the exposure in a narrative way. Risk of bias: The risk of bias will be assessed with the NTP/OHAT risk of bias rating tool for human and animal studies. We will use GRADE to assess the certainty of the conclusions (high, moderate, low, or inadequate) regarding the association between radiofrequency electromagnetic fields and oxidative stress. Funding: This work was funded by the World Health Organization (WHO). Registration: The protocol was registered on the PROSPERO webpage on July 8, 2021.